GLP‐1 suppresses glucagon secretion in human pancreatic alpha‐cells by inhibition of P/Q‐type Ca2+ channels. Issue 17 (5th September 2018) - Ramracheya, Reshma; Chapman, Caroline; Chibalina, Margarita; Dou, Haiqiang; Miranda, Caroline; González, Alejandro; Moritoh, Yusuke; Shigeto, Makoto; Zhang, Quan; Braun, Matthias; Clark, Anne; Johnson, Paul R.; et al.
Abstract: Glucagon is the body's main hyperglycemic hormone, and its secretion is dysregulated in type 2 diabetes mellitus (T2DM). The incretin hormone glucagon‐like peptide‐1 (GLP‐1) is released from the gut and is used in T2DM therapy. Uniquely, it both stimulates insulin and inhibits glucagon secretion and thereby lowers plasma glucose levels. In this study, we have investigated the action of GLP‐1 on glucagon release from human pancreatic islets. Immunocytochemistry revealed that only <0.5% of the α ‐cells possess detectable GLP‐1R immunoreactivity. Despite this, GLP‐1 inhibited glucagon secretion by 50–70%. This was due to a direct effect on α ‐cells, rather than paracrine signaling, because the inhibition was not reversed by the insulin receptor antagonist S961 or the somatostatin receptor‐2 antagonist CYN154806. The inhibitory effect of GLP‐1 on glucagon secretion was prevented by the PKA‐inhibitor Rp‐cAMPS and mimicked by the adenylate cyclase activator forskolin. Electrophysiological measurements revealed that GLP‐1 decreased action potential height and depolarized interspike membrane potential. Mathematical modeling suggests both effects could result from inhibition of P/Q‐type Ca 2+ channels. In agreement with this, GLP‐1 and ω ‐agatoxin (a blocker of P/Q‐type channels) inhibited glucagon secretion in islets depolarized by 70 mmol/L [K + ]o, and these effects were not additive. Intracellular application of cAMP inhibited depolarization‐evoked exocytosis in individual α ‐cells by a PKA‐dependent (Rp‐cAMPS‐sensitive) mechanism. We propose that inhibition of glucagon secretion by GLP‐1 involves activation of the few GLP‐1 receptors present in the α ‐cell membrane. The resulting small elevation of cAMP leads to PKA‐dependent inhibition of P/Q‐type Ca 2+ channels and suppression of glucagon exocytosis. Abstract : GLP‐1 suppresses glucagon secretion in human pancreatic alpha‐cells by inhibition of P/Q‐type Ca 2+ channels